Endogenous reparative pluripotent Muse cells with a unique immune privilege system: Hint at a new strategy for controlling acute and chronic inflammation - Kuroda, Yasumasa; Oguma, Yo; Hall, Kerrigan; Dezawa, Mari (Frontiers in Pharmacology, 2022)
Multilineage-differentiating stress enduring (Muse) cells, non-tumorigenic endogenous pluripotent stem cells, reside in the bone marrow (BM), peripheral blood, and connective tissue as pluripotent surface marker SSEA-3(+) cells. They express other pluripotent markers, including Nanog, Oct3/4, and Sox2 at moderate levels, differentiate into triploblastic lineages, self-renew at a single cell level, and exhibit anti-inflammatory effects. Cultured mesenchymal stromal cells (MSCs) and fibroblasts contain several percent of SSEA-3(+)-Muse cells. Circulating Muse cells, either endogenous or administered exogenously, selectively accumulate at the damaged site by sensing sphingosine-1-phosphate (S1P), a key mediator of inflammation, produced by damaged cells and replace apoptotic and damaged cells by spontaneously differentiating into multiple cells types that comprise the tissue and repair the tissue. Thus, intravenous injection is the main route for Muse cell treatment, and surgical operation is not necessary. Furthermore, gene introduction or cytokine induction are not required for generating pluripotent or differentiated states prior to treatment. Notably, allogenic and xenogenic Muse cells escape host immune rejection after intravenous injection and survive in the tissue as functioning cells over 6 and ∼2 months, respectively, without immunosuppressant treatment. Since Muse cells survive in the host tissue for extended periods of time, therefore their anti-inflammatory, anti-fibrotic, and trophic effects are long-lasting. These unique characteristics have led to the administration of Muse cells via intravenous drip in clinical trials for stroke, acute myocardial infarction, epidermolysis bullosa, spinal cord injury, neonatal hypoxic ischemic encephalopathy, amyotrophic lateral sclerosis, and COVID-19 acute respiratory distress syndrome without HLA-matching or immunosuppressive treatment.